PELATIHAN KETRAMPILAN KOMUNIKASI UNTUK MENURUNKAN EXPRESSED EMOTION KELUARGA PENDERITA SKIZOFRENIA - , DINDA PUSPASARI; , Drs. Subandi, MA., Ph.D., Psi. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Number of patients with schizophrenia and relapse rates at a worrying speed. Relapse in patients with schizophrenia is due to the high expressed emotion in families. The purpose of this study was to determine the effect of communication skills training to reduce expressed emotion families of schizophrenics. The hypothesis is a communication skills training can reduce expressed emotion in the families of schizophrenics. Participants were five family members of people with schizophrenia in Paguyuban Gelimasjiwo. The design used was one group pretest-posttest design. Data collection is done using a level of expressed emotion scale in families of people with schizophrenia who used for the pretest, post-test and follow-up. The results of non-parametric statistical analysis Wilcoxon Signed Rank indicates significant decrease of expressed emotion in the participants on the measurement of pretest and posttest with the z value = -2.032, p = 0.042 (p <0.05). The results showed that communication skills training can reduce the expressed emotion in families of schizophrenics.